Papers Presented at the Seventh Workshop on Empirical Studies of Programmers - ESP '97 1997
DOI: 10.1145/266399.266409
|View full text |Cite
|
Sign up to set email alerts
|

A glimpse of expert programmers' mental imagery

Abstract: There is widespread anecdotal evidence that expert programmers make use of visual mental images when they are designing programs. In this study, expert programmers were directly questioned regarding the nature of their mental representations while they were engaged in a design task. This investigative technique was used with the explicit intention of eliciting introspective reports of mental imagery. The resulting transcripts displayed a considerable number of common elements. These suggest that software desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Other studies suggest that developers form mental models of the structure, intent, and relationships in code, which guide their decision making [35], [51]. Some studies found that developers have a quickly degrading memory for such information [1], [17], explaining why developers rely so extensively on external memory sources, such as digital or paper notes and whiteboards [16], [39].…”
Section: Related Workmentioning
confidence: 99%
“…Other studies suggest that developers form mental models of the structure, intent, and relationships in code, which guide their decision making [35], [51]. Some studies found that developers have a quickly degrading memory for such information [1], [17], explaining why developers rely so extensively on external memory sources, such as digital or paper notes and whiteboards [16], [39].…”
Section: Related Workmentioning
confidence: 99%
“…A previous paper [44] describes a study into the mental imagery of ten individual expert software developers, who were questioned directly regarding the nature of their mental representations while they were engaged in a design task.…”
Section: Study 1: Software Developers' Mental Imagerymentioning
confidence: 99%
“…Elicitation of experts' mental imagery -of the ways they envision and manipulate software designs and programmes in their mindsreveals both that the imagery is rich and varied, and that there are strong commonalities among individuals in terms of the properties of their mental imagery (if not in the entirety of their repertoires) [Petre and Blackwell,29]. Mental imagery is used here to describe any inspectable mental representations, regardless of the sensory modality of the image.…”
Section: Mental Imagery and Software Visualisationmentioning
confidence: 99%